Evaluation of Point-of-Care-Directed Coagulation Management in Pediatric Cardiac Surgery - Zajonz, Thomas; Edinger, Fabian; Hofmann, Johannes; Yoerueker, Uygar; Akintürk, Hakan; Markmann, Melanie; Müller, Matthias (The Thoracic and Cardiovascular Surgeon, 2024)
Coagulatory alterations are common after pediatric cardiac surgery and can be addressed with point-of-care (POC) coagulation analysis. The aim of the present study is to evaluate a preventive POC-controlled coagulation algorithm in pediatric cardiac surgery.This single-center, retrospective data analysis included patients younger than 18 years who underwent cardiac surgery with cardiopulmonary bypass (CPB) and received a coagulation therapy according to a predefined POC-controlled coagulation algorithm. Patients were divided into two groups (<10 and >10 kg body weight) because of different CPB priming strategies.In total, 173 surgeries with the use of the POC-guided hemostatic therapy were analyzed. In 71% of cases, target parameters were achieved and only in one case primary sternal closure was not possible. Children with a body weight ≤10 kg underwent surgical re-evaluation in 13.2% (15/113), and respectively 6.7% (4/60) in patients >10 kg. Hemorrhage in children ≤10 kg was associated with cyanotic heart defects, deeper intraoperative hypothermia, longer duration of CPB, more complex procedures (RACHS-1 score), and with more intraoperative platelets, and respectively red blood cell concentrate transfusions (all p-values < 0.05). In children ≤10 kg, fibrinogen levels were significantly lower over the 12-hour postoperative period (without revision: 3.1 [2.9–3.3] vs. with revision 2.8 [2.3–3.4]). Hemorrhage in children >10 kg was associated with a longer duration of CPB (p = 0.042), lower preoperative platelets (p = 0.026), and over the 12-hour postoperative period lower platelets (p = 0.002) and fibrinogen (p = 0.05).The use of a preventive, algorithm-based coagulation therapy with factor concentrates after CPB followed by POC created intraoperative clinical stable coagulation status with a subsequent executable thorax closure, although the presented algorithm in its current form is not superior in the reduction of the re-exploration rate compared to equivalent collectives. Reduced fibrinogen concentrations 12 hours after surgery may be associated with an increased incidence of surgical revisions.
Keywords: transfusion; blood; cardiopulmonary bypass; CPB; pediatric; surgery; complications